High expression of SOX9 is a diagnostic and prognostic indicator of glioma - Xu, Libo; Wang, Zhenhao; Li, Mao; Li, Qingsong (Frontiers in Oncology, 2025)
BackgroundGlioblastoma (GBM) originates from neuroepithelial tissue and is one of the most common intracranial malignant tumors in adults, with high recurrence rate and poor prognosis. In recent years, SOX9 has been reported to play an important role in many diseases and cancers, and is a promising target, but it has been rarely reported in GBM.MethodsRNA sequencing data of GBM were obtained from the Cancer Genome Atlas (TCGA) database and the Genotype-Tissue Expression (GTEx) database for analysis of SOX9 expression and differentially expressed genes (DEGs). Moreover, functional enrichment analysis of GBM-related DEGs was performed by GO/KEGG, GSEA, and protein-protein interaction (PPI) network. Additionally, the clinical significance of SOX9 in GBM was assessed by Kaplan-Meier Cox regression and prognostic model. What’s more, we analyzed SOX9-related immune cell infiltration and expression of immune checkpoints in GBM. The incorporated studies were analyzed using the R package.ResultsSOX9 was highly expressed in a range of malignant tumor tissues, including GBM. Surprisingly, high SOX9 expression was remarkably associated with better prognosis in the lymphoid invasion subgroups in a sample of 478 cases (P < 0.05). Totally, 126 differentially significant genes (DSGs) were identified between high- and low- expression group, of which 29 genes were upregulated and 97 genes were downregulated. Furthermore, high expression of SOX9 was an independent prognostic factor for IDH (isocitrate dehydrogenase)-mutant in Cox regression analysis. Screening was performed by LASSO coefficients to select non-zero variables that satisfied the coefficients of lambda. min, and four genes were screened out. OR4K2 and IDH status were prognostic factors associated with THCA in multifactorial COX regression analysis. SOX9, OR4K2 and IDH status were included in the nomogram prognostic model. Correlation analysis indicated SOX9 expression was correlated with immune cell infiltration and expression of immune checkpoints in GBM.ConclusionSOX9 was identified as a diagnostic and prognostic biomarker in glioblastoma, particularly in IDH-mutant cases. Its expression was closely correlated with immune infiltration and checkpoint expression, indicating its involvement in the immunosuppressive tumor microenvironment. SOX9-based gene signatures further supported a robust nomogram model, underscoring its potential as a therapeutic and prognostic target in GBM.